Let Them Eat Cake: Why the Inherent Bias in Professor Grading Should Change to Individual Performance Assessments - Gower, Kim (Journal of Organizational Psychology, 2021)
Self-performance and other appraisal is a ubiquitous part of the organizational landscape in the U.S. If you ask employees, however, it is not a popular one. In viewing the way people are assessed from the start of grade school through professional careers, final performance evaluation is almost always in the hands of somebody else telling us our worth, and often without full context or information. Therefore, when it comes to writing and rating from a personal perspective, a lack of tools, including practice and objective self-assessment, can cause a serious impediment to an employee’s ability to achieve promotions, earn bonuses and raises, and further their professional progression. More importantly, assessments on individuals as done by others have brought about mounds of research on the inherent bias of such systems, at all levels. This paper examines that bias as it applies to professors grading their students’ work, and outlines teaching students, and business professionals, how to properly evaluate their performance and advocate for themselves as a valuable lifelong skill.